2012
DOI: 10.4329/wjr.v4.i3.75
|View full text |Cite
|
Sign up to set email alerts
|

Dural lesions mimicking meningiomas: A pictorial essay

Abstract: The purpose of this essay was to illustrate the radiological and pathological findings in a wide spectrum of dural lesions mimicking meningiomas. Familiarity with and knowledge of these findings will narrow the differential diagnosis and provide guidance for patient management. In this pictorial review, we describe the following entities: Solitary fibrous tumors, hemangiopericytoma, gliosarcoma, leiomyosarcoma, dural metastases, Hodgkin's disease, plasmocytoma, Rosai-Dorfman disease, neurosarcoidosis, melanocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 29 publications
0
16
0
3
Order By: Relevance
“…Patients were identified through institutional databases at both sites and were included in this report if they met the following criteria: 1) clinical presentation of a dural mass and no evidence of primary parenchymal brain involvement, 2) brain imaging demonstrating an extra-axial mass arising from the dura mater, 3) pathologic confirmation of lymphoma, 4) primary neurological presentation. Our review identified twenty six patients with DL, five of whom were reported previously (1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were identified through institutional databases at both sites and were included in this report if they met the following criteria: 1) clinical presentation of a dural mass and no evidence of primary parenchymal brain involvement, 2) brain imaging demonstrating an extra-axial mass arising from the dura mater, 3) pathologic confirmation of lymphoma, 4) primary neurological presentation. Our review identified twenty six patients with DL, five of whom were reported previously (1).…”
Section: Methodsmentioning
confidence: 99%
“…Due to their clinical and radiographical similarities to meningiomas or dural metastases, DLs are often misdiagnosed. (2, 4). Neuroimaging frequently identifies a single or multiple diffusely enhancing extra axial lesions with a dural tail (1).…”
Section: Introductionmentioning
confidence: 99%
“…İçerisinde akım sinyalsiz (flow void) alanlar görülür. Geniş tabanı ile duraya tutunabilir veya dar pedinküllü olabilir [51]. Dural metastazlar menenjiomları taklit edebilir (Resim 9).…”
Section: Menenjiomunclassified
“…T2A görüntülerde izo-hipointenstir. İVKM sonrası diffüz kontrastlanır [51]. Çok sayıda olabilir ve leptomeninksleri tutabilir.…”
Section: Menenjiomunclassified
See 1 more Smart Citation